Feasibility of plethysmography variability index (PVI) in determining intravascular volume in critically ill patients with acute kidney injury : a pilot study - Kian, Lee Eng (2017)
Background: Accurate and timely assessment of intravascular volume status in critically ill patients presenting with acute kidney injury remains a challenge despite the availability of various measurement modalities. Technically, these modalities are divided into two groups; dynamic and static modalities. This pilot study aims to investigate the correlation of plethysmographic variability index (PVI), a dynamic monitoring device with static modalities of central venous pressure (CVP) and inferior vena cava distensibility index (dIVC), and dynamic modalities of intra-arterial systolic pressure (IASBP) and pulse pressure variation (PPV) in the assessment intravascular volume status in critically ill patients with acute kidney injury. Methods: This was a prospective observational cross-sectional pilot study using convenient sampling.Total of 30 patients who were admitted to critical care facilities, intubated and diagnosed with acute kidney injury based on AKIN (full name) criteria and fulfilled study criteria were recruited in this study after consented by the legal guardian. The PVI, IASBP, CVP, dIVC and PPV values were collected at 8-hour interval for a period of 24 hours. Categorical variables were expressed in frequency and percentage while numerical variables were expressed in mean and standard deviation; statistical analysis was carried by SPSS version 22.0. p value of < 0.05 is considered statistically significant.Results: The mean age for patients included this study was 50 ± 19. PVI showed a statistically significant positive correlation with both static measurement dIVC and dynamic measurement PPV (p=<0.001). There were no correlation between PVI and CVP or IASBP.(CVP, p = 0.499 and IASBP, p value = 0.605). Conclusion: This pilot study demonstrates statistically significant correlation of PVI with dIVC and PPV but not with CVP or IASBP.